Design, optimization and economic viability of an industrial low temperature hot water production system in Algeria: A case study - Karim Kaci; Mustapha Merzouk; Nachida Kasbadji Merzouk; Mohammed Missoum; Mohammed El Ganaoui; Omar Behar; Rabah Djedjig (Center of Biomass & Renewable Energy, Diponegoro University, 2023)
Solar energy has a great potential in many areas of industrial activity in Algeria. This is because most of Algeria has high levels of sustainable solar insulation. Unfortunately, few industries use solar energy for hot water generation, but some industrial processes require hot water at temperatures that can be easily obtained from solar thermal panels. This paper presents a case study to investigate the technical and financial feasibility of a solar-powered industrial agro-processing system in Algiers. Based on the solar collectors connection type for which the economic feasibility study was carried out, an appropriate design of the system was determined. The latter was actually done by analyzing the levelized cost of energy savings. The design of the thermo-solar process is carried out based on F-chart method with a new approach by integrating the incidence angle modifier and of using real and experimental data requirements to determine realistic achievable performance of the solar process. The results showed that, in comparison to the currently used electrical system, the electrical energy savings achieved by the solar-powered system make it an economically viable option with a solar coverage rate of 80%. The investment depreciation balance shows that the use of such a thermal solar energy system will be more competitive than fossil fuels system if the price of electricity in the country increases from 0.048 to 0.075 €/kWh.